Asymmetric wage adjustment and employment in European firms - Petra Marotzke; Robert Anderton; Ana Bairrao; Clémence Berson; Peter Tóth (European Central Bank (ECB), 2017)
We explore the impact of wage adjustment on employment with a focus on the role of downward nominal wage rigidities. We use a harmonised survey dataset, which covers 25 European countries in the period 2010-2013. These data are particularly useful for this paper given the firm-level information on the change in economic conditions and collective pay agreements. Our findings confirm the presence of wage rigidities in Europe: first, collective pay agreements reduce the probability of downward wage adjustment; second, the rise in the probability of downward base wage responses following a decrease in demand is significantly smaller than the rise in the probability of an upward wage response associated with an increase in demand. Estimation results point to a negative effect of downward wage rigidities on employment at the firm level.
Keywords: J23; J30; 330; Wage rigidity; Employment; Demand shocks